2019
DOI: 10.1021/acs.jpca.9b06806
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Rainbows in the Rotationally Inelastic Scattering of NO with CH4

Abstract: Using a combination of velocity-map imaging and resonance-enhanced multi-photon ionization detection with crossed molecular beam scattering, the dynamics of rotational energy transfer have been examined for NO in collisions with CH4 at a mean collision energy of 700 cm 1. The images of NO scattered into individual rotational (j′NO) and spin-orbit () levels typically exhibit a single broad maximum that gradually shifts from the forward to the backward scattering direction with increasing rotational excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…If we focus on the 1600 m s −1 and 2500 m s −1 trajectories for the rotating NO molecules, there appears to be evidence for rotational rainbows, most interestingly in the case for the 2500 m s −1 which looks to display a ‘double rainbow’. Rotational rainbows from NO scattering have been observed experimentally in both the gas phase [27] and from solid surfaces [28] . Theoretical studies have shown the presence of rotational rainbows off graphite, though only at high surface temperatures [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…If we focus on the 1600 m s −1 and 2500 m s −1 trajectories for the rotating NO molecules, there appears to be evidence for rotational rainbows, most interestingly in the case for the 2500 m s −1 which looks to display a ‘double rainbow’. Rotational rainbows from NO scattering have been observed experimentally in both the gas phase [27] and from solid surfaces [28] . Theoretical studies have shown the presence of rotational rainbows off graphite, though only at high surface temperatures [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…Integral and differential scattering cross sections have been measured for a range of (oriented and unoriented) open-shell molecules and collision partners, in particular OH 46,[59][60][61][62][63] and NO. [64][65][66][67] The OH + Rg (Rg = rare gas) systems have been systematically studied by Scharfenberg et al, 62 who showed that the contribution of the spin-orbit excited states to the total scattering intensity significantly decreased with increasing polarizability and mass of the atom. This observation was in part correlated with the larger anisotropy and deeper attractive wells in the potentials for the heavier rare gases, suggesting that the more repulsive character of the PESs for the lighter atoms is conducive to spin-orbit excitations, which require an additional B140 cm À1 (relative to the spin-orbit conserving manifold) to be accessed.…”
Section: Introductionmentioning
confidence: 99%
“…38 Although the high-precision velocity control enabled by Stark or Zeeman decelerators clearly provides great benefits, it is possible to determine information on the DCS correlated with the degree of rotational excitation in the collision partner in more conventional crossed-beam VMI experiments. 39,40 Significant new mechanistic insight can still be provided by these lower-resolution experiments, as demonstrated by Sun et al, who uncovered a new mechanism in CO + CO inelastic scattering, in which both CO molecules experienced high rotational excitation while undergoing forward scattering, which they dubbed forward-scattered symmetric excitation (FSSE). Quasi-classical scattering calculations and comparison to CO + N 2 inelastic scattering, in which FSSE scattering was not observed, revealed that this mechanism was mediated by the dipole−dipole interaction in CO + CO. 41 Finally, we have also demonstrated angular scattering information as a function of (post-collision) collider internal energy for the NO(A, v = 0, j = 0.5) + N 2 system, with the NO optically prepared.…”
Section: ■ Introductionmentioning
confidence: 99%